THE IMPACT OF PERSONALITY VARIABLES IN POVERTY PERCEPTION - Palomar Lever, Joaquina; Cienfuegos Martínez, Yessica Ivet (Anales de Psicología / Annals of Psychology, 2006)
Although poverty is a phenomenon that affects millions of people around the world, there are a small number of studies that have examined people’s perception about poverty and the ways to overcome it. The purpose of this research was to study the perception that poor and non-poor people have about poverty, and also to study the relationship between the perception of poverty and psychological variables such as: perceived social support, depression, self-esteem, locus of control, achievement motivation, subjective well-being and coping. The sample was composed by 918 subjects; of which 612 were considered poor and 306 were non-poor. The results illustrate how participants perceive poverty as a consequence of structural factors. In both groups, there were statistical differences in some psychological variables according to the perceptions about the causes of poverty.